A Cross Talk between the Endocannabinoid System and Different Systems Involved in the Pathogenesis of Hypertensive Retinopathy - Farhan Khashim Alswailmi (MDPI AG, 2023)
The prognosis of hypertension leads to organ damage by causing nephropathy, stroke, retinopathy, and cardiomegaly. Retinopathy and blood pressure have been extensively discussed in relation to catecholamines of the autonomic nervous system (ANS) and angiotensin II of the renin-angiotensin aldosterone system (RAAS) but very little research has been conducted on the role of the ECS in the regulation of retinopathy and blood pressure. The endocannabinoid system (ECS) is a unique system in the body that can be considered as a master regulator of body functions. It encompasses the endogenous production of its cannabinoids, its degrading enzymes, and functional receptors which innervate and perform various functions in different organs of the body. Hypertensive retinopathy pathologies arise normally due to oxidative stress, ischemia, endothelium dysfunction, inflammation, and an activated renin-angiotensin system (RAS) and catecholamine which are vasoconstrictors in their biological nature. The question arises of which system or agent counterbalances the vasoconstrictors effect of noradrenaline and angiotensin II (Ang II) in normal individuals? In this review article, we discuss the role of the ECS and its contribution to the pathogenesis of hypertensive retinopathy. This review article will also examine the involvement of the RAS and the ANS in the pathogenesis of hypertensive retinopathy and the crosstalk between these three systems in hypertensive retinopathy. This review will also explain that the ECS, which is a vasodilator in its action, either independently counteracts the effect produced with the vasoconstriction of the ANS and Ang II or blocks some of the common pathways shared by the ECS, ANS, and Ang II in the regulation of eye functions and blood pressure. This article concludes that persistent control of blood pressure and normal functions of the eye are maintained either by decreasing systemic catecholamine, ang II, or by upregulation of the ECS which results in the regression of retinopathy induced by hypertension.